Effect of Ferronickel Slag Powder on Strength of Soil in Marine Environment - Feng Chen; Shenghao Tong (Advances in Civil Engineering)
Over the past few years, soil-cement has been widely used in marine geotechnical engineering; meanwhile, the safety of soil-cement in marine environment has attracted wide attention. In order to study the influence of composite ferronickel slag powder on the strength and micro morphology of soil-cement in marine environment, the composite nickel iron slag powder was added into the soil-cement in this paper. The unconfined compressive strength test, erosion resistance coefficient analysis, SEM, and EDS test analysis of soil-cement were carried out.. Results showed that the marine environment had great influences on the strength of soil-cement, and the addition of compound nickel-iron slag powder can enhance the strength of soil-cement, and the deterioration of the strength of soil-cement is reduced. In addition, the compound ferronickel slag powder has microaggregate effect, morphological effect, and activation effect, which not only improves compaction rate of soil-cement and prevents invasion of erosive ions in marine environment but also has positive effects on the performance of soil-cement.